Estudio etnográfico de las prácticas del cultivo de las tierras y la cooperación entre los comuneros de la comunidad Huanca Pallaguchi en la actualidad - Ortega Yupa, Elsa Susana (2022)
The research work entitled "Ethnographic study of the practices of land cultivation and cooperation among the community members of the Huanca Pallaguchi community at present" has the general objective of establishing similarities and differences between the practices of land cultivation and cooperation of the community members of the Huanca Pallaguchi community at present (2021), in comparison with the customary practices of the community, using an ethnographic study. It is research with an ethnographic method, analytical and historical-logical theoretical research methods, and descriptive and exploratory elements. The direct observation technique was used with the observation card instrument, the interview technique with the semi-structured questionnaire instrument, and the life history technique. For data analysis and processing, the following were used: tabulation of interviews, triangulation of information, cause-effect analysis, and force field analysis. It was established that after the dissolution of the Pallaguchi farm and its surroundings in 1987, the recovery of the ayllu way of life emerged with the practices of cooperation and reciprocity such as the Minka as community work allowed the organizational strengthening, the Minka between ayllu (families) guaranteed the disinterest in monetary exchange, in addition, the maki mañachina (lending of hands) in agricultural, daily, and festive tasks. The survival practices; the yunti (asking for grains) either in the chakra or in the time of Lent from house to house, the challenge; collecting the remains of the fallen grains of the sheaves or of what the chakrayuk (owner of the land) delivered, the chakrana; gathering tender fruits such as beans, peas, and corn, the wachu mañana (asking for potato furrows), the chituna; extracting delicate fruits from potatoes, geese, mashuwa and the melloco, the partir; sowing in halves between families who owned several plots of land, also by exchanges of ecological floors, they guaranteed survival and food sovereignty. Traditional agricultural practices such as associated cultivation, use of the yunta, traditional threshing, and others are recognized as an alternative for environmental sustainability, wellbeing of the chakra, and human health.